Calcineurin Inhibitor Nephrotoxicity Through the Lens of Longitudinal Histology: Comparison of Cyclosporine and Tacrolimus Eras. Issue 8 (August 2016) - Nankivell, Brian J.; P'Ng, Chow H.; O'Connell, Philip J.; Chapman, Jeremy R.
Abstract : Background: The contribution of calcineurin inhibitors (CNI) nephrotoxicity to progressive kidney transplant injury remains debated, with little long-term data from the modern tacrolimus (TAC) era using lower doses. Methods: This longitudinal cohort study evaluated histological evidence of CNI nephrotoxicity from normal donor kidneys of successful kidney-pancreas transplant recipients during cyclosporine (CSA) and TAC eras, analyzed by intention-to-treat. Results: From 200 patients, 1622 adequate prospective protocol (84.3%) and indication (15.7%) kidney biopsies yielded 8.1 ± 4.1 samples per patient, over 7.4 ± 4.4 years posttransplant. The TAC era demonstrated less rejection and reduced early immune-mediated tubular damage, compared with CSA ( P < 0.001). The incidences of acute mild arteriolopathy, striped interstitial fibrosis, glomerular congestion, and tubular microcalcification were all greater with CSA (hazard ratios of 1.70, 9.35, and 3.78, respectively) and maximal within the first posttransplant year, compared with TAC-treated patients ( P < 0.001). However, the 1-, 5-, and 10-year prevalence moderate arteriolar hyalinosis was similar: CSA was 5.4%, 38.4%, and 79.1%; and TAC was 4.3%, 33.6% and 77.2%, respectively ( P = NS). Morphometric measurement demonstrated lumenal narrowing from inwards collapse of hyalinized arteriolar walls unable to maintain its structural integrity. Severe hyalinosis was calculated to reduce arteriolar blood flow to 20 ± 34% of normal. Severity of arteriolar hyalinosis correlated with contemporaneous glomerulosclerosis (r = 0.44, P < 0.001), and subsequent progression in 1356 sequential biopsy pairs, consistent with glomerular ischemia. Conclusions: Tacrolimus-based therapy appeared superior to the CSA era, with less early CNI nephrotoxicity and fewer rejection episodes, but comparable chronic arteriolar toxicity. Calcineurin inhibitors are imperfect long-term maintenance immunosuppressive agents because of frequent and irreversible chronic toxicity. Abstract : This large, single-center, longitudinal cohort study compares histological changes in kidney-pancreas transplant recipients during CSA and TAC eras. Despite reduced early immune-mediated and CNI-associated changes, TAC-based therapy showed an indistinguishable time course of chronic arteriolar changes compared to CSA. Supplemental digital content is available in the text.